Perceptions of trust in the police: a cross-national comparison - Ruddell, Rick (International journal of comparative and applied criminal justice, 2023)
Comparative analyses enable researchers to identify individual- and structural-level factors that influence the operations of the justice system that might not be evident when examining these indicators in a single nation. In this study, the factors associated with the public’s self-reported trust in thepolice were examined in 105 nations. We analysed the contributions of three theoretical propositions: social integration, democratic performance, and self-reported perceptions of crime. With respect to the structural factors, the public expressed the most trust in the police in nations with a greater adherence to the rule of law and a higher per capita gross domestic product. Citizens in countries perceived to be more corrupt were also less likely to believe their police were trustworthy. Inconsistent with expectations, individual-level factors, such as perceptions about crime, risks of being victimised, and prior histories of victimisation also exerted an influence on the public’s perceptions of trust. .